In vivo phenotypic drug discovery: applying a behavioral assay to the discovery and optimization of novel antipsychotic agents12. Issue 6 (10th May 2016) - Shao, Liming; Campbell, Una C.; Fang, Q. Kevin; Powell, Noel A.; Campbell, John E.; Jones, Philip G.; Hanania, Taleen; Alexandrov, Vadim; Morganstern, Irene; Sabath, Emily; Zhong, Hua M.; Large, Thomas H.; et al.
Abstract : A mouse-based assay (SmartCube) was used for both screening and lead optimization of a novel antipsychotic. Abstract : Phenotypic drug discovery (PDD) is increasingly being recognized as a viable compliment to target-based drug discovery (TDD). By measuring functional changes, typically at a systems level, PDD can facilitate the identification of compounds having a desirable pharmacology. This capability is particularly important when studying CNS diseases where drug efficacy may require modulation of multiple targets in order to overcome a robust, adaptive biological system. Here, we report the application of a mouse-based high-dimensional behavioral assay to the discovery and optimization of a structurally and mechanistically novel antipsychotic. Lead optimization focused on optimizing complex behavioral features and no explicit effort was made to identify the target (or targets) involved.